P Pengembangan Media Pembelajaran Pedom Cah dengan Pendekatan Kontekstual pada Materi Pecahan - Sari, Wiwin Purnama; Khoiriyah, Lathifatul; Pasha, M Kemal; Amanda, Lidya Desma; Khoiriyah, Siti (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
Changes in education are one of the major impacts of the development of information technology. Technology has transformed the learning process from conventional to modern approaches. One innovation that can be applied is integrating learning media with technology. One such innovation is "Pedom Cah", a contextual approach-based learning media for teaching fractions. This media combines technology in the form of e-books with physical teaching aids. This study aims to develop learning media that is feasible, effective, and practical for fourth-grade students at SD Negeri 1 Wonoharjo. The research follows the Research and Development (R&D) method using the 4-D model (Define, Design, Develop, Disseminate). Data were collected through media validation, learning observations, student questionnaires, and learning outcome tests. The results of media validation obtained an average score of 4.00, exceeding the feasibility threshold of >3.00. The learning implementation achieved an average score of 87.5%, student activity scored 80.07%, student learning tests scored 84%, and student responses reached 91%. Based on these findings, it is concluded that "Pedom Cah" is a feasible, effective, and practical learning media for teaching mathematics in the classroom. This research contributes to the development of innovative, technology-based learning media that enhances student engagement and learning outcomes in mathematics.